The Frequency with which Creativity Develpment Strategies are used in Various Fields: Research on Attitudes among Preschool Teachers - Sturza Milić, Nataša; Nedimović, Predrag; Sturza, Svetlana (Revija za elementarno izobraževanje, 2018)
The aim of the paper was to examine the attitudes of preschool teachers towards strategies for creative thinking. We also examined how often these strategies were used in everyday work with children. Specificaims were to gain insight into the differences between preschool teachers, depending on the age groups of the children with whom they work, and depending on the length of their work experience. Another aim was to examine whether these strategies were directed towards the development of creative behavior in various educational fields. The results of this research can be expected to contribute to the creation of better conditions for more frequent application of creativity development strategies in a variety of domains and anincrease in the sensitivity of preschool teachers for the understanding and promotion of a holistic approach to creativity at an early age.DOI: 10.18690/rei.11.3.201 -214.2018COBISS-ID:
Keywords: creativity development strategies; early development; holistic approach